An evaluation of the feasibility of a transoral endotracheal intubation method in mice using a combination of commercially available research equipment - SASAKI, Kazumasu; ITO, Takuya; SHIGA, Takuya; UEMURA, Kazunori; ISHIKAWA, Tatsuya (Journal of Veterinary Medical Science, 2025)
Endotracheal intubation plays a crucial role in airway management in mice. Transoral endotracheal intubation (TEI) offers a less invasive alternative to tracheostomy and is more ideal for chronic experiments. Despite the development of various TEI techniques in mice, the lack of accessible and well-established methods that do not require specialized equipment hinders routine research. We developed a feasible and highly successful method for TEI in C57BL/6JJcl mice using a combination of commercially available research equipment. A success rate of 97.5% was achieved within 21.2 ± 8.9 sec (mean [standard deviation]) with no observed complications in the 40 mice studied. This method simplifies TEI without specialized tools and provides practical guidance for consistent application in routine research settings.